STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBASIS PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR PONTIANAK SELATAN - Wahyuningsih, Deti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study is aimed to describe about Contextual Teaching and Learning Strategies on the Integrated Thematic-Based Learning In Class III B of Elementary School 03 in South Pontianak. This research is a descriptive research using qualitative approach. The Subjects in this study were teachers and students in class III B of Elementary School 03 in South Pontianak. Data collection was done by observation, interview, and documentation. Data analysis was done through the stages of: data reduction, data display, and conclusion. The Technique examination of data validity is by using triangulation. The result of this research showed that the implementation of learning strategy of Contextual Teaching and Learning Strategies on the Integrated Thematic-Based Learningwas found some positive actions that teachers had  inspired the students to link the material they taught to the real-world situations of the students and encouraged students to make connections between theirknowledge and the application in their daily life. Keywords: Learning Strategy, Contextual Teaching and Learning,Integrated thematic learning.